The Impact of Incentives on Job Performance, Business Cycle, and Population Health in Emerging Economies - Liu, Wei; Liu, Yaoping (Frontiers in Public Health, 2022)
In the past, there are different researchers that conducted research on incentives that how it was linked with employee motivation influencing emerging economies. This study is addressing two gaps that were recommended by previous studies. One research gap is focusing on how future research should focus more on employee loyalty and employee engagement and that needs to be explored more with business cycle. One gap was recommended for future researchers to use different moderators between incentives, health of employees and job performance with population health. This was kept in focus more to identify the responses of hospitals and physicians to the business cycle involved. For this purpose, this study was conducted in order to see the impact of incentives on job performance and health of workers in public and private sector hospitals in Shandong, Eastern China. Data were collected in the form of questionnaires that consisted of close ended questions. These questionnaires were then filled out by 171 doctors and 149 nurses working in both public and private sector in Shandong, Eastern China. The results showed that there is a relation between different variables. Some variables have more impact on other variables such as transformational leadership has a significant impact on the job performance and business cycle whereas monetary incentives were also impacting the job performance and population health, but the impact was lower than that of the transformational leadership for the job performance influencing emerging economies.